DOUBLE PUNISHMENT IN THE WAITING TIME FOR DEATH PENALTY: A STUDY OF HUMAN RIGHTS PROTECTION IN INDONESIA - Sidabukke, Sahat Marulitua (Universitas Pelita Harapan, 2023)
In Indonesia, until 2022 there were 428 people who have been sentenced with death penalty by anaesthetics and were still waiting for their execution to be carried out. Among those people, 101 have been sitting in the death row for more than 10 years. This means that those who are sentenced to death by the court (inkracht van gewijsde) were imprisoned for life until their execution. They had to carry out two kinds of punishments, videlicet death penalty and imprisonment. There is a lengthy waiting time, which results in the neglect of death row convicts' rights. This is a normative juridical research with data collected through literature study, court decision analysis, and concept test in focus group discussion attended by Supreme Prosecutor, Supreme Court, National Narcotics Agency, State Police of Republic of Indonesia and National Commission of Human Rights. The result of this research shows that such waiting period creates distrust between judicial institutions. It also creates uncertainty and becomes a loophole for death row inmates to apply for unlimited legal remedies which causes delay of the execution of the death penalty. On the other hand, the role of the Public Prosecutor as the executioner of death penalty is not yet optimal. Because of the two reasons above (legal remedies and political will), they worry about potentially being considered as violating human rights.